An examination into the nature of satisfaction formation in a continually delivered business service context. - Briggs, Elten. (My University, 2006)
The next two papers are empirical pieces that test different portions of the conceptual framework. Data for both papers were collected from the customers of third-party logistics (3PL) service providers via an online survey instrument. The first empirical piece re-examines the relationship between global satisfaction and loyalty in light of the conceptual framework using structural equation modeling (SEM). The findings suggest that the positive relationship commonly observed between satisfaction and loyalty is more complex in CDBS contexts than has previously been acknowledged. The second empirical piece tests for the importance of velocity performance---i.e. the rate at which performance is changing (Hsee and Abelson 1991)---to satisfaction formation using regression analyses. The findings confirm the importance of velocity performance and illustrate how environmental conditions moderate its influence.

The dissertation follows a three paper format. The first paper is a conceptual piece that offers a framework for global satisfaction formation in CDBS contexts. Customer satisfaction is one of the fundamental concepts in the marketing discipline, but existing theoretical frameworks have been constructed based primarily on research in discrete contexts involving consumers. Theoretical insights are drawn from expectancy disconfirmation and social exchange theory.

This research examines the process of customer satisfaction formation in a business-to-business services context where delivery occurs on an ongoing or continual basis. The setting is referred to as a continually delivered services (CDBS) context. It is expected that more and more exchanges in marketing will resemble those currently occurring in CDBS contexts in upcoming years (Rust 2004).
Keywords: Consumer satisfaction.; Industrial marketing.; Business Administration, Marketing.